Soil enzymes in response to climate warming: Mechanisms and feedbacks. (9th March 2022) - Fanin, Nicolas; Mooshammer, Maria; Sauvadet, Marie; Meng, Cheng; Alvarez, Gaël; Bernard, Laëtitia; Bertrand, Isabelle; Blagodatskaya, Evgenia; Bon, Lucie; Fontaine, Sébastien; Niu, Shuli; Lashermes, Gwenaelle; et al.
Abstract: Soil enzymes are central to ecosystem processes because they mediate numerous reactions that are essential in biogeochemical cycles. However, how soil enzyme activities will respond to global warming is uncertain. We reviewed the literature on mechanisms linking temperature effects on soil enzymes and microbial communities, and outlined a conceptual overview on how these changes may influence soil carbon fluxes in terrestrial ecosystems. At the enzyme scale, although temperature can have a positive effect on enzymatic catalytic power in the short term (i.e. via the instantaneous response of activity), this effect can be countered over time by enzyme inactivation and reduced substrate affinity. At the microbial scale, short‐term warming can increase enzymatic catalytic power via accelerated synthesis and microbial turnover, but shifts in microbial community composition and growth efficiency may mediate the effect of warming in the long term. Although increasing enzyme activities may accelerate labile carbon decomposition over months to years, our literature review highlights that this initial stage can be followed by the following phases: (a) a reduction in soil carbon loss, due to changing carbon use efficiency among communities or substrate depletion, which together can decrease microbial biomass and enzyme activity and (b) an acceleration of soil carbon loss, due to shifts in microbial community structure and greater allocation to oxidative enzymes for recalcitrant carbon degradation. Studies that bridge scales in time and space are required to assess whether there will be an attenuation or acceleration of soil carbon loss through changes in enzyme activities in the very long term. We conclude that soil enzymes determine the sensitivity of soil carbon to warming, but that the microbial community and enzymatic traits that mediate this effect change over time. Improving representation of enzymes in soil carbon models requires long‐term studies that characterize the response of wide‐ranging hydrolytic and oxidative enzymatic traits—catalytic power, kinetics, inactivation—and the microbial community responses that govern enzyme synthesis. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.